The degree of possession of islamic education teachers in public schools In Taybeh and Al- Wasatiyah Districts in Irbid governorate for the skill of building behavioral goals from the point of view of principals - Aljadayah, Rahmeh Ibrahim Tayel (Journal of Educational and Psychological Sciences, 2022)
This study aimed to identify the degree of possession of Islamic Education teachers of the skill of building behavioral goals from the point of view of the principals In public schools in the Taybeh and Al- Wasatiyah Districts in Irbid Governorate. To achieve the objectives of the study, the researcher used the descriptive survey approach, the sample of study consisted from (50) female and male principals, and a questionnaire for data collection; it consisted of (28) statements, distributed for five sector. The results indicated that the degree of possession of Islamic Education teachers of the skill of building behavioral goals from the point of view of the principals In public schools in the Taybeh and Al- Wasatiyah Districts Was High with average (3.81 out of 5), at the level of domains; The formulation of cognitive goals obtained the highest average (4.01), then the scope of criteria for formulating goals with an average of (3.80), and thirdly, the conditions for formulating goals with an average of (3.79), then the psychomotor goals with an average of (3.75) and finally the emotional goals with an average of (3.70) and all of them with a degree (high), Furthermore, there were no statistical significant differences at (α≤ 0.05) in the variable of principal's sex. However, there were statistically significant differences due to the years of experience in favor of (11 years and more). Based on the results, the researcher made a number of recommendations to develop the skill of formulating behavioral goals among teachers in the Taybeh and Al- Wasatiyah brigades and the whole of the Kingdom of Jordan, in addition to suggestions for future studies on the subject.
Keywords: Skill of Building; Behavioral Goals; School Principals; Teachers; Islamic Education